On the Cohomology of Spaces of Links and Braids via Configuration Space Integrals - Volić, Ismar (Sarajevo Journal of Mathematics, 2024)
We study the cohomology of spaces of string links and braids in... 2000 Mathematics Subject Classification. Primary: 57M27; Secondary: 81Q30, 57R40